2023
DOI: 10.1177/23247096231158951
|View full text |Cite
|
Sign up to set email alerts
|

Severe Central Airway Obstruction Secondary to a Giant Endobronchial Hamartoma: A Case Report

Abstract: Central airway obstruction refers to the occlusion of more than 50% of the trachea, main stem bronchi, or lobar bronchus. It can potentially become a life-threatening condition. Pulmonary hamartomas (PH) are rare tumors with an incidence of 0.25%, constituting about 8% of all benign lung neoplasms. Only 10% of PH occur endobronchially, while the remaining appear peripherally. We present the case of a women with an endobronchial hamartoma that required emergent resection by bronchoscopy. This is 44-year-old wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Immunocompromised conditions, such as poorly controlled diabetes mellitus, are known to be associated with CPA 18 . Poorly controlled blood glucose levels can result in dysfunction of T cells, neutrophils, and humoral immunity, prompting susceptibility to various opportunistic infections 9 . Previous studies demonstrated that diabetes is a significant risk factor for both IPA and CPA 8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunocompromised conditions, such as poorly controlled diabetes mellitus, are known to be associated with CPA 18 . Poorly controlled blood glucose levels can result in dysfunction of T cells, neutrophils, and humoral immunity, prompting susceptibility to various opportunistic infections 9 . Previous studies demonstrated that diabetes is a significant risk factor for both IPA and CPA 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite these findings, no case reports have specifically addressed this correlation to date. Moreover, while diabetes is recognized as a risk factor for both CPA and invasive pulmonary aspergillosis (IPA), 9,10 the impact of strict blood sugar control on reducing CPA activity and preventing hemoptysis recurrence remains unclear.…”
Section: Introductionmentioning
confidence: 99%